Antimalarials as antivirals for COVID-19: Believe it or not! (2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus responsible for the coronavirus disease -19 (COVID-19). Since December 2019, SARS-CoV-2 has infected millions of people worldwide, leaving hundreds of thousands dead. Chloroquine (CQ) and Hydroxychloroquine (HCQ) are antimalarial medications that have been found to have in vitro efficacy against SARS-CoV-2. Several small prospective studies have shown positive outcomes. However, this result has not been universal, and concerns have been raised regarding the indiscriminate use and potential side effects. The clinicians are conflicted regarding the usage of these medications. Appropriate dose and duration of therapy are unknown. Here, we will discuss the pharmacokinetic and pharmacodynamic properties of CQ and HCQ, as well as review the antiviral properties. The manuscript will also examine the available data from recent clinical and preclinical trials in order to shed light on the apparent inconsistencies.